Ekstrak Air Rumput Kebar (Biophytum petersianum Klotzch) sebagai Penghambat Perkembangan Telur Cacing Gastrointestinal Ruminansia Secara in Vitro - Alnita Baaka; Isti Widayati; Noviyanti Noviyanti (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2017)
Gastrointestinal worm disease in cattle is scathing for the breeder’s as it lowers cattle’s productivity and inflict major economic loss. Furthermore, the interraction between cattle, man and the environment might bringout the risk of zoonotic diseases (diseases which can spread between man and animals). Kebar grass contains phytochemical elements such as alkaloid, saponin, tanin, glycoside and flavonoid. Those elements have the potentialas an alternate anthelmentic in the effort to utilize the endemic biodiversities of Papua. This research is performed at Faculty of Animal Husbandry Animal Health Laboratory and Faculty of Math and Natural Science MicrobiologyLaboratory of Universitas Papua, for 8 months. The leaves and the stems of the kebar grass were collected and stored at room temperature. The Kebar grass extract was divided into 3 parts, i.e. fresh extract, wind dried extractand sun dried extract. Fresh fecal samples were collected and examined with the native method. The samples where nematodes eggs are found is treated with kebar grass extract. As a comparison, positive control is made withoxfendazole and negative control is made nematodes larvae fertilization. Fecal cultures and grass extract mixture is left alone for 7 days in room temperature and examined under microscope with 400x fortification to see whetnerthere is any development of the nematodes’ eggs. The obstained data is analyzed by tabulation and descriptive method. The result is the samples mixed with kebar grass extract show no development of nematodes’ egg. As acomparison, the negative control which is observed with baerman method shows development of nematodes’ eggs. It can be concluded that the effect of kebar grass extract can deters nematodes’ egg development.